The chemistry and technology of petroleum - Speight, James G. (Boca Raton : CRC Press, Taylor & francis Group, 2014)
"The success of the 1st, 2nd, 3rd, and 4th Editions of this text has been the primary factor in the decision to publish a fifth edition. In addition, the demand for petroleum products, particularly liquid fuels (gasoline and diesel fuel) and petrochemical feedstocks (such as aromatics and olefins), is increasing throughout the world. Traditional markets such as North America and Europe are experiencing a steady increase in demand whereas emerging Asian markets, such as India and China, are witnessing a rapid surge in demand for liquid fuels"--
Includes bibliographical references and index.
Keywords: Petroleum; Petroleum -- Refining; Petroleum chemicals; SCIENCE / Chemistry / Industrial & Technical